Microbial Interaction as a Determinant of the Quality of Supply Drinking Water: A Conceptual Analysis - Towhid, Syeda T. (Frontiers in Public Health, 2018)
This conceptual analysis elucidates the microbial interaction inside municipal distribution pipes, subsequent deterioration in the quality of the supply water and its impacts on public health. Literature review involved a total of 21 original reports on microbiological events inside the water distribution system were studied, summarizing the current knowledge about the build-up of microbes in treated municipal water at various points of the distribution system. Next, original reports from the microbiological analysis of supply water from Bangladesh were collected to enlist the types of bacteria found growing actively. A schematic diagram of microbial interaction among the genera was constructed with respect to the physical, chemical and microbiological quality of the supply water. Finally latest guidelines and expert opinions from public health authorities around the world are reviewed to keep up with using cutting-edge molecular technology to ensure safe and good quality drinking water for municipal supply.